From molecular design to 3D printed life-like materials with unprecedented properties. (June 2017) - Wu, D.J.; Bouten, C.V.C.; Dankers, P.Y.W.
Abstract: Stimuli-responsive synthetic materials have gained interest as biomaterials due to their ability to transform upon external stimuli. In order to mimic the cellular microenvironment synthetically, it is proposed that stimuli-responsiveness needs to be coupled with hierarchical supramolecular assembly of the materials applied. Additionally the mechanical properties of the microenvironment, i.e. the extracellular matrix, determine the nature of the tissue, which also needs to be mimicked in the material. Full control of mechanical properties, stimuli-responsiveness and hierarchical structure formation is proposed to be achieved by 3D printing of supramolecular systems into hierarchical structures that are able to react and adapt to stimuli, using metamaterial concepts. Therefore, in this review we discuss 3D printing of stimuli-responsive materials, and the design and development of metamaterials. Combination of these concepts with supramolecular chemistry is proposed to result in the design and synthesis of life-like biomaterials with unprecedented properties. Highlights: 3D-printed synthetic scaffolds as extracellular matrix mimics. Stimuli-responsive materials combined with metamaterial properties. Supramolecular chemistry for modular and dynamic control at various length scales.